Qualidade de vida dos farmacêuticos atuantes em hospitais brasileiros durante a pandemia de Covid-19 - Adriano, Liana Silveira (2024)
During the COVID-19 pandemic, pharmacists have experienced various psychological impacts that can directly affect their professional quality of life. This study aimed to evaluate the professional quality of life of Brazilian hospital pharmacists two years after the start of the pandemic and characterize associated factors. This is a cross-sectional study conducted through online survey in Brazil between April and July 2022. Initially, a questionnaire with 23 questions was constructed, featuring three sections: 1-Sociodemographic profile; 2-Work characteristics; and 3-Perceptions related to COVID-19. The validation of the questionnaire was carried out by specialist pharmacists. Responses were assessed using the Content Validity Index of each item (I-CVI; Desired ≥ 0.78) and Content Validity Index of the scale (S-CVI; Desired ≥ 0.9). All ICVI analyses were found to be acceptable (I-CVI > 0.78, total S-CVI-clarity = 0.97, total SCVI-relevance = 0.99), with the content considered 'valid' for investigating factors associated with the pharmacist's professional quality of life in the context of the COVID-19 pandemic. The questionnaire application stage was conducted in a sample of 237 pharmacists. The validated questionnaire was used along with the Professional Quality of Life Scale, validated version for Brazil, which assesses Compassion Satisfaction (CS), Compassion Fatigue (CF), and Burnout (BO). ANOVA and t-test were used for group comparisons, bootstrapping for normality correction, and Kolmogorov-Smirnov and Shapiro-Wilk tests to check normality of distribution. Most respondents reported moderate or high levels of CS (71.3%), BO (78.9%), and CF (72.2%). Females had higher CF values (d = 0.45). Single individuals had higher CF [(ΔM = 0.32; 95% CI Bca (0.1 – 0.58)] and BO [(ΔM = 0.53; 95% CI Bca (0.19 – 0.89)] values than married ones. Pharmacists aged 40-49 showed lower BO values than those aged 20-29 [(ΔM = -0.74; 95% CI Bca (-1.15 – -0.35)] and 30-39 [(ΔM = 0.49; 95% CI Bca (-0.87 – - 0.16)]; professionals working more than 44 hours had higher BO values than those working up to 36 hours [(ΔM = 0.54; 95% CI Bca (0.14 – 0.95)]. The study showed that Brazilian hospital pharmacists reported moderate levels of BO, CF, and CS. Gender, marital status, age group, and working hours were identified as factors associated with BO and CF.